The Role of the Mining Sector in Regional Economic Development: A Case Study of East Kutai Regency - Ardhan Ismail; Dea Mierela Ananda; Agus Winarno; Revia Oktaviani; Arif Setiawan; Rety Winonazada; Supriyanto Supriyanto (International Journal of Engineering, Science and Information Technology, 2025)
This study examines the role of the mining sector in East Kutai Regency's regional economic development, where mining contributes over 40% to GRDP. An integrated analytical framework combining Input-Output analysis with overlay analysis techniques (Location Quotient, Klassen Typology, and Shift-Share) was employed to comprehensively assess the mining sector's structural position, inter-sectoral linkages, and development impact. The Input-Output analysis utilized East Kalimantan's 2016 table updated via RAS method to generate regency specific coefficients, while overlay analysis employed GRDP statistics for 2014 to 2023 to evaluate spatial concentration and competitive dynamics. Input-Output findings reveal the mining sector exhibits weak backward linkage of 1.0 and forward linkage of 0.95, positioning it in Quadrant III with minimal inter-sectoral integration and limited multiplier effects on the regional production system. Overlay analysis through Location Quotient demonstrates the mining sector's highest comparative advantage at 1.76, indicating strong export orientation and spatial concentration. However, Klassen Typology classifies it in Quadrant IV as a lagging sector with growth coefficient of 0.94 and contribution coefficient of 0.93, reflecting stagnant development performance. Shift-Share analysis within the overlay framework confirms the mining sector's severe competitiveness decline at negative 35,714.67, the worst among seventeen evaluated sectors. The convergent results from Input-Output and overlay analyses indicate the mining sector operates as an extractive enclave with insufficient value-added generation and constrained developmental spillovers. Enhancing the mining sector's developmental role requires strengthening backward and forward linkages through downstream processing facilities, local content requirements, and technology transfer mechanisms to transform the sector from an extractive enclave into an integrated regional growth driver.